Lemyra elena, a new species from Sichuan, south-western China (Lepidoptera, Erebidae, Arctiinae) - Saldaitis, Aidas; Volynkin, Anton V.; Dûda, Juozas (Zootaxa, 2018)
The genus Lemyra Walker, 1856 belongs to the tribe Arctiini of the subfamily Arctiinae Leach, 1815 (family Erebidae Leach, 1815). The genus was revised by Thomas (1990). At present it is subdivided into two subgenera, Lemyra and Thyrgorina Walker, [1865] and includes more than 100 valid species, many of which were described during last three decades (Fang 1993; Inoue 1993; Tshistjakov & Kishida 1994; Kirti & Gill 2008; Černý 2011; 2014; Černy & Pinratana 2009; Dubatolov 2007; 2010; Kirti & Singh 2016).